A sandwich-like structural model revealed for quasi-2D perovskite films. Issue 16 (29th March 2021) - Zheng, Fei; Hall, Christopher R.; Angmo, Dechan; Zuo, Chuantian; Rubanov, Sergey; Wen, Zhenchuan; Bradley, Siobhan J.; Hao, Xiao-Tao; Gao, Mei; Smith, Trevor A.; Ghiggino, Kenneth P.
Abstract : Quasi-2D perovskite films deposited on hot substrates are shown to possess a sandwich-like, large- n /small- n /large- n phase distribution profile in the orthogonal direction. This structure facilitates both exciton funneling to the film surfaces and efficient charge carrier transport. Abstract : The excellent performance and stability of perovskite solar cells (PSCs) based on quasi-2D Ruddlesden–Popper perovskites (RPPs) holds promise for their commercialization. Further improvement in the performance of 2D PSCs requires a detailed understanding of the microstructure of the quasi-2D perovskite films. Based on scanning transmission electron microscopy (STEM), time-resolved photoluminescence, and transient absorption measurements, a new sandwich-like structural model is proposed to describe the phase distribution of RPPs. In contrast to the conventional gradient distribution, it is found that small- n RPPs are sandwiched between large- n RPP phase layers at the front and back sides owing to crystallization initiated from both interfaces during film formation. This sandwich-like distribution profile facilitates excitons funneling from the film interior to both surfaces for dissociation while free carriers transport via large- n channels that permeate the film to ensure efficient charge collection by the corresponding electrodes, which is favorable for high-performance photovoltaics. This discovery provides a new fundamental understanding of the operating principles of 2D PSCs and has valuable implications for the design and optimization strategies of optoelectronic devices based on quasi-2D RPPs films.